METODE MAKE A MATCH DALAM PEMBELAJARAN AQIDAH AKHLAK DI MADRASAH IBTIDAIYAH - Titin Suprihatin (Al-Aulad: Journal of Islamic Primary Education, 2018)
The purpose of this study is to analyze student learning outcomes before using the method of learning make a match, describe the implementation of learning process Akidah Akhlak material behave commendable using the method of learning make a match, and describe student learning outcomes after using the method of learning make a match on the subjects Akidah Akhlak the material behaves commendable in the fourth class of MIS Cikulu. Make a match is an active learning method to deepen or train the learned material. Students are asked to look for pairs of cards which are answers or specific material questions in the lesson. One of the advantages of this technique is students looking for a partner while learning about a concept or topic in a fun atmosphere. This research uses Classroom Action Research method. Respondents in this study as many as 15 students of class IV MIS Cikulu Sukahurip Village, Pangandaran District, Pangandaran City. Based on the results of data analysis from the evaluation of students on subjects Akidah Akhlak material behave commendably by using the method of learning make a match obtained student learning outcomes in cycle I with an average value of 68.67 and on cycle II with an average value of 88. Thus there is a significant increase in the learning process by using the method of learning make a match on the subject Akidah Akhah material behave commendably between cycles I and II.